A Posterior Anal Sling for Fecal Incontinence: Results of a 152-Patient Prospective Multicenter Study. Issue 8 (August 2016) - Mellgren, Anders; Zutshi, Massarat; Lucente, Vincent R.; Culligan, Patrick; Fenner, Dee E.
Abstract : (Abstracted from Am J Obstet Gynecol 2016;214:349.e1–349.e8) Accidental bowel leakage or fecal incontinence (FI) affects between 0.4% and 18% of the general population, with the probability increasing with age. Large population studies estimate that 5% to 10% of all American adult women have FI.